Petroleum resins for bitumens modification - Grynyshyn, Oleg; Bratychak, Michael; Krynytskiy, Volodymyr; Donchak, Volodymyr (Publishing House of Lviv Polytechnic National University, 2008)
The process of tar and industrial petroleum resin "Piroplast-2" joint oxidation has been investigated. The experimental results of the main regularities researches of the obtaining process of petroleum resins with carboxyl groups based on the pyrocondensate C9 fraction of hydrocarbon feedstock pyrolysis have been shown. It has been established that synthesized petroleum resins may be used for the modification of petroleum bitumens. Вивчено процес сумісного окиснення гудрону та промислової нафтополімерної смоли "Піропласт-2". Наведено результати експериментальних досліджень основних закономірностей процесу одержання нафтополімерних смол з карбоксильними групами на основі фракції С9 піроконденсату піролізу вуглеводневої сировини. Встановлено, що створені нафтополімерні смоли можуть бути використані для модифікації нафтових бітумів.
Використання нафтополімерних смол для модифікації бітумів
Keywords: tar; blown bitumen; petroleum resin; carboxyl group; modification; bituminous-polymeric composition; гудрон; окиснений бітум; нафтополімерна смола; карбоксильна група; модифікація; бітумно-полімерна композиція